A study on the role of trust factor in adopting personalised medicine. Issue 7 (2nd July 2020) - Misra, Subhas Chandra; Bisui, Sandip; Singh, Arpit
ABSTRACT: Despite all the potential that Personalised Medicine (PM) has in reducing healthcare costs and treatment errors, as well as in bringing about significant improvement in the mode of healthcare, the adoption rate of Personalised Medicine is not yet up to the mark. Some research has been done in the area of Personalised Medicine and several new drugs have been already discovered. However, adequate research is yet to be performed to sort out various hurdles that are hindering implementation of this novel medicare system on a larger scale. One of the hurdles is the so-called trust factor. In the present paper, it has been our endeavour to investigate whether the trust issues have a moderating effect on the success of adoption of personalised medicine. A survey-based post facto methodology has been adopted for this purpose. Responses have been collected from a number of people, who are medical practitioners/medical researchers/pharmacists/regulatory board members/patients. The dataset obtained thereby has been analysed by using advanced statistical techniques and modern statistical software packages. The study indicates that the trust issues have a significant moderating effect on the successful adoption of personalised medicine.